2005
DOI: 10.1103/physrevb.72.045317
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and electronic characterization of methyl-terminated Si(111) surfaces by high-resolution synchrotron photoelectron spectroscopy

Abstract: The chemical state, electronic properties, and geometric structure of methyl-terminated Si͑111͒ surfaces prepared using a two-step chlorination/alkylation process were investigated using high-resolution synchrotron photoelectron spectroscopy and low-energy electron diffraction methods. The electron diffraction data indicated that the methylated Si surfaces maintained a ͑1 ϫ 1͒ structure, where the dangling bonds of the silicon surface atoms were terminated by methyl groups. The surfaces were stable to annealin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
267
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(308 citation statements)
references
References 48 publications
38
267
2
Order By: Relevance
“…SiÀC bonds on Si(111) and Si(100) have been shown to produce less than 0.2 eV band bending. [33,43,83] Furthermore, the observed inversion [20] in n-SiÀalkyl/Hg (Fig. 3) and n-SiÀOÀalkyl/Hg junctions [88] (see Section 4.2) implies that the Si surface is not pinned, supporting the idea that CÀSi and CÀOÀSi surface terminations effectively passivate the Si surface both chemically (preventing oxidation) and electronically (small density of surface states).…”
Section: Passivation Of Surface Statesmentioning
confidence: 64%
See 3 more Smart Citations
“…SiÀC bonds on Si(111) and Si(100) have been shown to produce less than 0.2 eV band bending. [33,43,83] Furthermore, the observed inversion [20] in n-SiÀalkyl/Hg (Fig. 3) and n-SiÀOÀalkyl/Hg junctions [88] (see Section 4.2) implies that the Si surface is not pinned, supporting the idea that CÀSi and CÀOÀSi surface terminations effectively passivate the Si surface both chemically (preventing oxidation) and electronically (small density of surface states).…”
Section: Passivation Of Surface Statesmentioning
confidence: 64%
“…Among the alkyls only CH 3 can replace each H on H-terminated Si, maintaining a relaxed (1 Â 1) structure for Si (111) [83] as the Si atom surface density on the (111) face is too high for a Si:alkyl ratio of 1:1 with longer alkyls. Therefore, while a C 1 (ÀCH 3 ) layer can have nearly 100% coverage, [84] longer alkyl chains form monolayers with a density of adsorbed molecules of about 1:2, [85] with the remaining Si atoms bound to H. [77,85] The longer the alkyl chain is, the stronger is the intermolecular (van der Waals) interaction and the less commensurate is the monolayer structure with the original Si surface.…”
Section: Siàc Bond Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…This orientation should produce diagnostic signatures and polarizations in the vibrational spectrum of such surfaces. Recent scanning tunneling microscopy 8 and low-energy electron diffraction studies 9 have revealed both short-range and long-range order on CH 3 -terminated Si surfaces. However, at present no information is available on the structure of surfaces terminated with alkyls such as C 2 H 5 -that are sterically precluded from terminating every atop site on an unreconstructed Si(111) surface.…”
Section: Introductionmentioning
confidence: 99%